Research on electromagnetic ultrasonic guided wave and eddy current composite detection method for cracks in aircraft aluminum alloy thin-wall sheet - MA Miandong; YU Hongwei; MA Rong; ZHOU Xin; FAN Xueling (Hangkong gongcheng jinzhan)
During the long-term service of aircraft, aluminum alloy thin-walled plates will generate a large number of cracks, which requires rapid and effective detection. Based on electromagnetic ultrasound and electromagnetic eddy current technology, an electromagnetic ultrasound guided wave eddy current composite detection method for aircraft aluminum alloy thin-walled plates is proposed, and the crack composite detection experiments on large-area aluminum alloy thin-walled plates are studied. The influence of electromagnetic ultrasound guided wave rapid detection ability and probe characteristics are analyzed, and the effectiveness of eddy current in detecting defects in thinwalled parts is evaluated. The results show that the proposed detection method can reduce the effective detection area to a certain extent, improve the detection efficiency, and achieve all-round and efficient detection of defects in aluminum alloy thin-walled plates. The changes in the probe lift distance and the number of magnets significantly can significantly affect the strength and quality of the detection signal. Absolute eddy current detection probes have two good detection frequency ranges. The optimal detection frequency range for differential eddy current detection probes is 500 kHz to 1 000 kHz.